2016
DOI: 10.1177/1756283x16643242
|View full text |Cite
|
Sign up to set email alerts
|

Current approaches for optimizing the benefit of biologic therapy in ulcerative colitis

Abstract: As biologic-based medication options for ulcerative colitis expand, our understanding of their optimal use in clinical practice is advancing as well. The appropriate use of combination therapy with immunomodulators can reduce the immunogenicity of biologic agents and raise serum drug levels of the biologic. A treat-to-target strategy with objective assessments of disease activity clearly defines the goals of biologic drug treatment. Mucosal healing is an evolving treatment goal and is associated with long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…In the sera and colonic tissues of UC patients, the levels of IL-1β, IL-6 and TNF-α were significantly higher than those of normal subjects, while down-regulation of them could prevent UC ( Galli et al, 2011 ; Roberts-Thomson et al, 2011 ; Groeger et al, 2013 ). Clinically, tocilizumab, the IL-6 receptor (IL-6R) antibody, has been used to treat UC ( Nishimoto et al, 2008 ; Wu et al, 2015 ); TNF-α antibody is also effective for UC management, especially for severe disease, and its bio-similars are confirmed with well safety and efficacy ( Sofia and Rubin, 2016 ; Komaki et al, 2017 ). Therefore, repairment of mucosal barrier and inhibition of inflammation are effective strategies for UC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the sera and colonic tissues of UC patients, the levels of IL-1β, IL-6 and TNF-α were significantly higher than those of normal subjects, while down-regulation of them could prevent UC ( Galli et al, 2011 ; Roberts-Thomson et al, 2011 ; Groeger et al, 2013 ). Clinically, tocilizumab, the IL-6 receptor (IL-6R) antibody, has been used to treat UC ( Nishimoto et al, 2008 ; Wu et al, 2015 ); TNF-α antibody is also effective for UC management, especially for severe disease, and its bio-similars are confirmed with well safety and efficacy ( Sofia and Rubin, 2016 ; Komaki et al, 2017 ). Therefore, repairment of mucosal barrier and inhibition of inflammation are effective strategies for UC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, two biological classes are available for the treatment of UC: TNF antagonists (infliximab, adalimumab, and golimumab) and anti-integrin therapy (vedolizumab) [ 76 ]. The development of biologic therapies for the treatment of UC has added an important treatment option, particularly for moderate to severe disease that does not respond to other therapies [ 2 , 76 , 77 ]. Studies of patient preferences have also reported that patients with UC strongly prefer medical therapy to surgical intervention [ 78 , 79 ].…”
Section: Current Misunderstandingsmentioning
confidence: 99%
“…To prevent LOR during maintenance treatment with mAb drugs, clinical research has led to new institutional recommendations for dosing in IBD treatment. These efforts are well-documented in publications (45)(46)(47), and encompass approved mAb drugs with diverse mechanisms of action.…”
Section: Development Of Anti-drug Antibodiesmentioning
confidence: 99%